2021
DOI: 10.1161/circulationaha.120.048728
|View full text |Cite
|
Sign up to set email alerts
|

Primary Results From the Understanding Outcomes With the S-ICD in Primary Prevention Patients With Low Ejection Fraction (UNTOUCHED) Trial

Abstract: Background: The Subcutaneous ICD (S-ICD) is safe and effective for sudden cardiac death prevention. However, patients in previous S-ICD studies had fewer comorbidities, less left ventricular dysfunction and received more inappropriate shocks (IAS) than in typical transvenous (TV)-ICD trials. The UNTOUCHED trial was designed to evaluate the IAS rate in a more typical, contemporary ICD patient population implanted with the S-ICD using standardized programming and enhanced discrimination algorithms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 32 publications
12
159
2
2
Order By: Relevance
“…Overall complications rates over 1 year and 18 months follow‐up were not found to be impacted by the incision technique in predictor models for the PAS study 9 nor the UNTOUCHED study, 10 respectively. In this study, no difference in the rate of infection or pocket complications was noted between the 2IT and 3IT group.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Overall complications rates over 1 year and 18 months follow‐up were not found to be impacted by the incision technique in predictor models for the PAS study 9 nor the UNTOUCHED study, 10 respectively. In this study, no difference in the rate of infection or pocket complications was noted between the 2IT and 3IT group.…”
Section: Discussionmentioning
confidence: 92%
“…IAS rates were not found to be significantly different between the two‐ and three‐incision groups in the Brouwer study, 7 and a low IAS rate of 2.8% was found over the 21‐month follow‐up in the Migliore study 12 . In contrast, IAS in the UNTOUCHED trial 10 recently demonstrated an association to 2IT, with 18 month rate of 4.9% versus the 2.5% in those patients implanted with 3IT. Prescribed high rate programming and use of the most recent device iterations in this study may be important differences leading to this finding of a small but statistically significant difference, although technique is likely a major factor for IAS occurrence and may also explain differences between studies.…”
Section: Discussionmentioning
confidence: 95%
“…Besides challenging vascular access (central veins stenosis, occlusion, AVF, or CVC for HD) and complications avoidance, the following indications for S-ICD placement should be considered: prior complications with transvenous ICDs, infection (bacteremia), and the young age of the ICD patient. Results published for randomized clinical trials support S-ICD use [61,62]. Koman et al reported data from the follow-up of 18 HD patients and 78 non-HD patients with implanted S-ICD.…”
Section: Cieds In a Patient On Hemodialysismentioning
confidence: 99%
“…Concerning the latter, the UNTOUCHED study of primary prevention ICD therapy supports the PRAE-TORIAN data by showing an inappropriate shock-free rate of 95.9%, suggesting that the new SMART PASS filter technology and appropriate high rate S-ICD programming may minimize inappropriate shocks in S-ICD recipients. 55 jom klase I. ili IIa. za ICD terapiju za primarnu ili sekundarnu prevenciju, uz razdoblje praćenja od 49,1 mjesec.…”
Section: Praetorian Compared Transvenous and Subcutaneousmentioning
confidence: 99%